The Effect of Thin Capitalization and Fixed Asset Intensity on Tax Avoidance with Institutional Ownership as a Moderation Variable - Yanti, Yanti; Dwi Astuti, Christina (Green Publisher Indonesia, 2023)
In this study, the authors are interested in examining how the Thin Capitalization and fixed asset intensity influence tax avoidance with Institutional Ownership as a moderating variable. Population of all manufacturing companies in the consumer industry sector listed on the Indonesia Stock Exchange from 2018 to 2021 which found 192 samples, according to the criteria needed in this study that were sampled for 2018 to 2021. The results that Thin Capitalization has a positive effect on tax avoidance, fixed asset intensity has a positive effect on tax avoidance. For the moderating variable, Institutional Ownership is not able to weaken the effect of Thin Capitalization on tax avoidance and Institutional Ownership is not able to weaken the effect of fixed asset intensity on tax avoidance